Unexpected Performance of Physical Mixtures over Solid Dispersions on the Dissolution Behavior of Benznidazole from Tablets - Leonardi, Darío (2013)
This work investigated the feasibility of developing benznidazole (BZL) tablets, allowing fast, reproducible, and complete drug dissolution, by compressing BZL-Polyethylene Glycol (PEG) 6000 physical mixtures (PMs) and solid dispersions (SDs). SDs were prepared by the solvent evaporation method at different drug:polymer ratios (w/w). BZL-PEG 6000 formulations were characterized by X-ray diffraction (XRD), scanning electron microscopy, and dissolution studies. The preparation of SD-based BZL tablets by the wet granulation method was carried out and the influence of pregelatinized starch (PS) and starch (S) on the disintegration time and drug dissolution rate was analyzed. SDs showed a significant improvement in the release profile of BZL as compared with the pure drug. As demonstrated by XRD, the crystalline character of BZL remained almost unaltered in both PMs and SDs. BZL release from the PEG 6000 tablets increased by the presence of PS instead S. Unexpectedly, the BZL release from tablets containing PMs was almost equal as compared with the BZL release from tablets containing SDs. In conclusion, the results suggest that PEG 6000 and PS are suitable additives for the development of BZL tablets with enhanced dissolution behavior through the preparation of ordinary PMs, instead the laborious SDs.